On the Approximate Controllability for Hilfer Fractional Evolution Hemivariational Inequalities. (19th May 2019) - Wang, JinRong; Liu, Xianghu; O'Regan, D.
Abstract: The paper is concerned with the approximate controllability of some Hilfer fractional evolution hemivariational inequalities. Using two classes of operators and their fundamental properties, we derive sufficient conditions for approximate controllability of linear and semilinear controlled systems via a fixed point theorem for multivalued maps. Finally, an example is given to illustrate our theory.